Prevalence and factors influencing sensorineural hearing loss among type II diabetes mellitus patients - Rajamani, Shanmugasundaram; Senniappan, Shivakumar; Radhakrishnan, Shankar (International Journal of Advances in Medicine, 2018)
Background: The typical hearing loss described among diabetes patients is progressive, bilateral, sensorineural deafness of gradual onset that predominantly affects the higher frequencies. Although there is mounting evidence for a relationship between diabetes and hearing impairment the awareness of auditory organ involvement in the course of diabetes is still not widespread among healthcare providers involved in diabetes care. Objective of present study was to assess the prevalence and the factors influencing sensorineural deafness among the patients with type II diabetes mellitus. Methods: A cross-sectional study was conducted at our hospital for a period of 6 months. All type II diabetes patients without any other major systemic illness (CVA, coronary artery disease, thyroid disorders) were included for the study. A total of 300 patients were included in our study and the informed consent was obtained from all the study participants. A detailed history related to hearing loss and diabetes status was elicited from all the patients. All basic blood investigations along with HbA1c was performed on all the patients. All the patients were subjected to pure tone audiometry and it was performed using a pure tone audiometer model AUL 12096 audiometer of Labat company in a sound proof room. Results: The total prevalence of sensori-neural deafness among the study subjects was found to be 51.3% with majority of them having mild to moderate degree of sensori-neural deafness. Increase in age, female gender, longer duration of diabetes and higher HbA1C levels are the factors which had influenced the state of sensorineural deafness among the study subjects. Conclusions: The use of audiological test at primary care level should be made mandate for screening all the diabetes patients for hearing loss such a way the quality of life can be improved for patients requiring therapeutic interventions for their hearing improvement.